1998
DOI: 10.1002/(sici)1097-4628(19980919)69:12<2377::aid-app9>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Studies of temperature influence on volatile thermal degradation products of poly(ethylene terephthalate)

Abstract: ABSTRACT:The temperature influence on the thermal degradation products evolved from poly(ethylene terephthalate) (PET) was investigated. The experiments were carried out within the temperature range of 200-700ЊC in air. The main volatile toxic products and weight losses during thermal degradation of PET were determined. The results are presented on plots as a function of the degradation temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 2 publications
0
37
0
1
Order By: Relevance
“…For each of the substances, the mass evolved from 1 g of PET was calculated. 26 The dependence of the evolved substances masses on the degradation temperature is shown in Figures 3-8.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For each of the substances, the mass evolved from 1 g of PET was calculated. 26 The dependence of the evolved substances masses on the degradation temperature is shown in Figures 3-8.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum yield of acetaldehyde was observed in nitrogen at a higher temperature than in air (400°C). 26 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of poly(ethylene terephthalate) (PET) granules, acetaldehyde and formaldehyde were shown to be emitted following thermal degradation at 200-300°C, with a wider range of VOCs detected after degradation at higher temperatures (Dzieciol & Trzeszczynski, 1998). Mixtures of low-molecular weight compounds extracted from samples of commercial rubber were shown by GC-MS analysis to contain small hydrocarbon fragments -evidence of polymer chain scission (Delaunay-Bertoncini et al, 2004).…”
Section: Using Voc Analysis To Understand Polymer Degradationmentioning
confidence: 99%
“…The temperature was selected because of the thermal analysis showed that it assures complete decomposition of polyethylene when the maximum amounts of products are formed. Amounts of particular products collected were recalculated to determine the yield from 1 g PE [12,13]. Percentage shares of particular components of the PE decomposition products are specified in Table 1.…”
Section: Analysis Of Products Of the Pyrolysis Of Polyethylene Waste mentioning
confidence: 99%